2010
DOI: 10.1037/a0018072
|View full text |Cite
|
Sign up to set email alerts
|

Do African American mothers really “love” their sons and “raise” their daughters?

Abstract: This study assessed 1500 adolescents from the National Longitudinal Study of Youth to test the hypothesis that African American mothers differentially socialize their girls and boys. The results showed that later-born boys had fewer chores, argued more with their mothers, lived in less cognitively stimulating homes, and were not allowed to make the same decisions as were the girls or firstborn boys at the same age. The later-born boys were also lowest in achievement and highest in externalizing behaviors. Pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 37 publications
4
66
2
Order By: Relevance
“…37 in addition, it has been suggested AfricanAmerican parents socialize youth differently based on the child's sex, with more demands being placed on girls than boys (e.g., greater monitoring, higher educational expectations). 38,39 evidence supports the effect of differential socialization of boys versus girls on youth health behaviors. 30,[40][41][42] in one qualitative study, African-American girls reported receiving more emotional and negative P a r e n t i n g C on text (p ar e n t in g s t y l e , support (e.g., being required to take care of and play outside with siblings) from parents for PA than boys, who reported receiving more tangible support.…”
Section: Introductionmentioning
confidence: 81%
“…37 in addition, it has been suggested AfricanAmerican parents socialize youth differently based on the child's sex, with more demands being placed on girls than boys (e.g., greater monitoring, higher educational expectations). 38,39 evidence supports the effect of differential socialization of boys versus girls on youth health behaviors. 30,[40][41][42] in one qualitative study, African-American girls reported receiving more emotional and negative P a r e n t i n g C on text (p ar e n t in g s t y l e , support (e.g., being required to take care of and play outside with siblings) from parents for PA than boys, who reported receiving more tangible support.…”
Section: Introductionmentioning
confidence: 81%
“…For purposes of the current study, child gender was treated as a control variable, however, parenting practices (Hill, 2006; Mandara, Varner, & Richman, 2010) and conduct problems (Deater-Deckard & Dodge, 1997; Florsheim, Tolan, & Gorman-Smith, 1996) have been shown to vary by gender. An extension of this work could be to assess the differences within externalizing problems between ethnic minority boys and girls, given differences in parenting and experience with discrimination (Brody et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it may be that parents are more vigilant in the parenting of their daughters. Another explanation for this double standard may be partially explained by Mandara et al’s (2010) suggestion that a possible cause for the high rates of African American male drug use, risky sexual behavior, and conduct problems compared with their sisters may be partly due to their mothers’ strict parenting (e.g., monitoring, etc.) of daughters but not sons.…”
Section: Discussionmentioning
confidence: 99%